What to Expect When You’re Expecting Zika - Lazear, Helen M. (Cell Host Microbe, 2017)
The 2015 emergence of Zika virus (ZIKV) in the Americas brought new attention to this previously obscure virus. Experimental model systems have been instrumental in rapidly advancing our understanding of ZIKV pathogenesis. Here, Lazear looks back on the events leading to the development of the ZIKV mouse model reported in Cell Host & Microbe.